Mitochonic Acid-5 Inhibits Reactive Oxygen Species Production and Improves Human Chondrocyte Survival by Upregulating SIRT3-Mediated, Parkin-dependent Mitophagy - Xin, Ruobing; Xu, Yiyang; Long, Dianbo; Mao, Guping; Liao, Hongyi; Zhang, Ziji; Kang, Yan (Frontiers in Pharmacology, 2022)
Mitochondrial dysfunction is related to the pathogenesis of osteoarthritis (OA); however, there are no effective drugs to treat OA for maintaining mitochondrial homeostasis. Studies have shown that mitochonic acid-5 (MA-5) has a protective effect against mitochondrial damage and plays a role in mitophagy. However, it is not clear whether MA-5 has a beneficial effect on inflammatory articular cartilage. Here, human OA cartilage was obtained from patients undergoing total joint replacement. Interleukin-1β (IL-1β) was used to stimulate chondrocytes and induce inflammatory injury. Cell Counting Kit-8, TUNEL, and flow cytometry assays were used to assess apoptosis. Gene expression was examined using quantitative reverse transcription-polymerase chain reaction. Mitochondrial function was evaluated using immunoblotting, mitochondrial membrane potential assay, JC-1 staining, and immunofluorescence analysis. Mitophagy was detected using immunoblotting and immunofluorescence. 3-(1H-1,2,3-triazol-4-yl) pyridine (3-TYP), a specific inhibitor of Sirtuin 3 (SIRT3), was used to block the SIRT3/Parkin pathway. Mitophagy in the cartilage sections was evaluated via immunohistochemistry. IL-1β was found to induce chondrocyte apoptosis by inhibiting SIRT3 expression and mitophagy. In addition, inflammatory damage reduced the mitochondrial membrane potential and promoted the production of intracellular reactive oxygen species (ROS), leading to increased mitochondrial division, mitochondrial fusion inhibition, and the consequent mitochondrial damage. In contrast, the MA-5 treatment inhibited excessive ROS production by upregulating mitophagy, maintaining the mitochondrial membrane potential, and reducing mitochondrial apoptosis. After chemically blocking SIRT3 with 3-TYP, Parkin-related mitophagy was also inhibited, an effect that was prevented by pretreatment of the chondrocytes with MA-5, thereby suggesting that SIRT3 is upstream of Parkin. Overall, MA-5 was found to enhance the activity of SIRT3, promote Parkin-dependent mitophagy, eliminate depolarized/damaged mitochondria in chondrocytes, and protect cartilage cells. In conclusion, MA-5 inhibits IL-1β-induced oxidative stress and protects chondrocytes by upregulating the SIRT3/Parkin-related autophagy signaling pathway.